Long-chain saturated fatty acids in breast milk are associated with the pathogenesis of atopic dermatitis via induction of inflammatory ILC3s - Weng Sheng Kong (Nature Portfolio, 2021)
Abstract Breastfeeding influences the immune system development in infants and may even affect various immunological responses later in life. Breast milk provides a rich source of early nutrition for infant growth and development. However, the presence of certain compounds in breast milk, related to an unhealthy lifestyle or the diet of lactating mothers, may negatively impact infants. Based on a cohort study of atopic dermatitis (AD), we find the presence of damage-associated molecular patterns (DAMPs) activity in the mother’s milk. By non-targeted metabolomic analysis, we identify the long-chain saturated fatty acids (LCSFA) as a biomarker DAMPs (+) breast milk samples. Similarly, a mouse model in which breastfed offspring are fed milk high in LCSFA show AD onset later in life. We prove that LCSFA are a type of damage-associated molecular patterns, which initiate a series of inflammatory events in the gut involving type 3 innate lymphoid cells (ILC3s). A remarkable increase in inflammatory ILC3s is observed in the gut, and the migration of these ILC3s to the skin may be potential triggers of AD. Gene expression analysis of ILC3s isolated from the gut reveal upregulation of genes that increase ILC3s and chemokines/chemokine receptors, which may play a role in ILC migration to the skin. Even in the absence of adaptive immunity, Rag1 knockout mice fed a high-LCSFA milk diet develop eczema, accompanied by increased gut ILC3s. We also present that gut microbiota of AD-prone PA milk-fed mice is different from non-AD OA/ND milk-fed mice. Here, we propose that early exposure to LCSFAs in infants may affect the balance of intestinal innate immunity, inducing a highly inflammatory environment with the proliferation of ILC3s and production of interleukin-17 and interleukin-22, these factors may be potential triggers or worsening factors of AD.